Charlie Cook's favorite book - Donaldson, Julia; Scheffler, Axel (London : Macmillan Children's Books, 2006)
A circular tale in which each new book character is reading about the next, beginning and ending with Charlie Cook.
3.5
K-3.
K-3
Keywords: Books and reading -- Juvenile fiction; Books and reading -- Fiction; Stories in rhyme; Books and reading -- Fiction; Stories in rhyme